Around-the-clock USD/MXN volatility: Macroeconomic announcement spillovers and FX market intervention mechanisms - Wilfrido Jurado Pedroza (Banco de México, 2021)
This paper advances the literature on the dynamics of the U.S. Dollar-Mexican Peso (USD/MXN) volatility process by leveraging high-frequency data. First, it documents the factors that characterize the intraday volatility process of the USD/MXN exchange rate at high frequencies based on a sample of five-minute returns from 2008 to 2017. Second, it empirically identifies the effects and the relative impact on the USD/MXN volatility process of various macroeconomic announcements, at different frequencies. The results conclude that the most impactful releases are associated with the monetary policy announcements by the Federal Reserve and Banco de México, together with the publication of some U.S. and China macroeconomic data. Furthermore, the results suggest that the different mechanisms implemented by Mexico's FX Commission have accomplished their objective of stabilizing the volatility of the USD/MXN.
Keywords: E5; F31; G12; G14; 330; FX Volatility; Heteroscedasticity; Macroeconomic Announcements; High-Frequency Data